(In)formal distribution channels in Romania during the 1980s: Entrepreneurial foreign students within the Second Economy - Bardan, Alexandra (CURRENTS OF HISTORY, 2022)
This article explores the role of entrepreneurial foreign students in the entangled informal networks of the second economy in Romania during the 1980s by questioning an underexplored part of the distribution chain, namely the provision of commodities missing or in short supply which further fueled the black market. Using a network analysis that traced improbable connections, we identified an unexpected channel in the form of international trade fairs, seen here as potential occasions where informal links are most likely to be first realized. The case study figured the second economy as a transnational place where various actors competed in the generation of hard currency.Summary: Beneficiaries of the dynamic policy of Socialist Romania that aimed to open to the world its prestigious higher education, foreign students enrolled in universities throughout the country were facing during the 1980s the prospects of shortages and missing commodities, similar to the large majority of the Romanian population. However, given their status as foreigners, they had access to Western products that most locals were deprived of, because they could purchase scarce goods from the hard currency stores. Entrepreneurial students further resold merchandise in high demand on the black market. The paper proposes a methodological framework inspired by network analysis, and centers the investigation on the actors of the informal networks of the second economy by asking how the entrepreneurial foreign students provisioned the commodities that were subsequently resold. The trade fairs organized by the “Peter Justensen” company, a Danish duty-free order house for diplomats, in 1985, 1986 and 1987 highlighted these type of events as potential occasions where informal commercial links are most likely to be first realized. In 1987, purchases were made not only by members of diplomatic missions but also by foreign students from all university centers, aided by the former to place orders that were reserved exclusively to holders of a diplomatic identification. The foreign students’ incidental involvement in the commercial transactions of the “Peter Justesen” exhibition of 1987 frames the second economy of a socialist country as a transnational place, revealing a more complex picture as compared to current narratives on the topic.